2014
DOI: 10.4049/jimmunol.1400216
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Suppresses Immune Effector Functions in Human Papillomavirus-Associated Epithelial Hyperplasia

Abstract: Persistent infection with high-risk human papillomaviruses (HPV) causes epithelial hyperplasia that can progress to cancer, and is thought to depend on immunosuppressive mechanisms that prevent viral clearance by the host. IL-17 is a cytokine with diverse functions in host defense and in the pathology of autoimmune disorders, chronic inflammatory diseases and cancer. We analyzed biopsies from patients with HPV- associated cervical intraepithelial neoplasia (CIN) grade 2/3 and murine skin displaying HPV16 E7 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 51 publications
7
59
1
1
Order By: Relevance
“…3b). Baseline levels of IL-17A in untreated K14.E7 skin were also higher than those in C57BL/6 skin, as reported previously [24]. Thus, in addition to Th2 cytokines, IL-17A was induced in K14.E7 skin in response to DNCB.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…3b). Baseline levels of IL-17A in untreated K14.E7 skin were also higher than those in C57BL/6 skin, as reported previously [24]. Thus, in addition to Th2 cytokines, IL-17A was induced in K14.E7 skin in response to DNCB.…”
Section: Resultssupporting
confidence: 66%
“…A recent study in our laboratory suggested that expression of HPV16.E7 oncoprotein leads to elevated production of IL-17A in the skin of K14.E7 mice and hyperplastic cervical tissue [24]. To date, there is no evidence in the literature that HPV16.E7 protein can directly affect the transcription of arginase.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DNCB-treated K14.E7 skin secreted more IL-17A into the skin explant supernatant than wild-type skin (Figure 3.3b). Base levels of IL-17A in untreated K14.E7 skin were also higher than that in C57BL/6 skin, as reported previously (35). Thus, in addition to Th2 cytokines, IL-17A was induced in K14.E7 skin in response to DNCB.…”
Section: Il-17a Is Specifically Induced In Dncb-treated K14e7 Skin Isupporting
confidence: 86%
“…In contrast, a recent study using HPV16 E7 trangenic skin transplantation has shown that IL-17A produced by CD4 + T cells is responsible for the suppression of immune effector functions (35).…”
Section: Cd4mentioning
confidence: 91%
See 1 more Smart Citation